2008
DOI: 10.1111/j.1365-2966.2008.13709.x
|View full text |Cite
|
Sign up to set email alerts
|

Orbital evolution of an accreting millisecond pulsar: witnessing the banquet of a hidden black widow?

Abstract: We have performed a timing analysis of all the four X-ray outbursts from the accreting millisecond pulsar SAX J1808.4-3658 observed so far by the Proportional Counter Array on board the Rossi X-ray Timing Explorer. For each of the outbursts, we derived the best-fitting value of the time of ascending node passage. We find that these times follow a parabolic trend, which gives an orbital-period derivative P(orb) = (3.40 +/- 0.18) x 10(-12)ss(-1), and a refined estimate of the orbital period, P(orb) = 7249.156 49… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(154 citation statements)
references
References 42 publications
6
147
1
Order By: Relevance
“…The exact trigger of the reflare is uncertain-they appear spontaneously in the simulations of Dubus et al (2001), although they do not resemble the observed reflares and they are seen by Hameury et al (2000) where reflares are caused by an increased irradiation of the donor star that causes a superoutburst (so called because their duration is much larger than that of normal outbursts) followed by reflares. The donor star in SAX J1808.4−3658 is observed to be strongly irradiated during quiescence (Homer et al 2001;Burderi et al 2003;) and indeed there are suggestions that it is losing a large amount of mass (di Salvo et al 2008; see however Hartman et al 2008 for criticisms of this strong mass loss scenario in SAX J1808.4 −3658 ). Another suggestion for the reflare trigger comes from the mass reservoir model of Osaki et al (2001), where reflares are triggered also after superoutbursts as long as the effective viscosity of the disk (parametrized by the α parameter) remains large through the entire sequence of reflares.…”
Section: The Origin Of Reflaresmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact trigger of the reflare is uncertain-they appear spontaneously in the simulations of Dubus et al (2001), although they do not resemble the observed reflares and they are seen by Hameury et al (2000) where reflares are caused by an increased irradiation of the donor star that causes a superoutburst (so called because their duration is much larger than that of normal outbursts) followed by reflares. The donor star in SAX J1808.4−3658 is observed to be strongly irradiated during quiescence (Homer et al 2001;Burderi et al 2003;) and indeed there are suggestions that it is losing a large amount of mass (di Salvo et al 2008; see however Hartman et al 2008 for criticisms of this strong mass loss scenario in SAX J1808.4 −3658 ). Another suggestion for the reflare trigger comes from the mass reservoir model of Osaki et al (2001), where reflares are triggered also after superoutbursts as long as the effective viscosity of the disk (parametrized by the α parameter) remains large through the entire sequence of reflares.…”
Section: The Origin Of Reflaresmentioning
confidence: 99%
“…Since SAX J1808.4−3658 has a measured dipolar magnetic field (at the poles) of 2×10 8 G(di Salvo et al 2008;Hartman et al 2008), it is possible to estimate the location of its magnetospheric radius. We first define the magnetospheric radius r m as the point where the magnetic field is strong enough to enforce co-rotation of gas in a thin Keplerian disk: …”
Section: Accretion Flow Geometrymentioning
confidence: 99%
“…IGR J18245-2452, observed as an accreting MSP and an eclipsing RMSP at different times (Papitto et al 2013), is the prototype of this class. A transition to a rotation-powered state during X-ray quiescence has also been proposed for a number of accreting MSPs on the basis of the observed spin-down (Hartman et al , 2009(Hartman et al , 2011Patruno 2010;Papitto et al 2011;Patruno et al 2012b), reprocessed optical emission Campana et al 2004;Di Salvo et al 2008 (Di Salvo et al 2008;Burderi et al 2009;Patruno et al 2012b), even if radio and γ-ray pulsations have not been detected so far (Burgay et al 2003;Iacolina et al 2009Iacolina et al , 2010Xing & Wang 2013). On the other hand, state transitions to an accretion stage have only been observed from eclipsing RMSPs (see above); these sources are the only possible candidates to undergo such fast transitions because the companion star has to spill matter through the inner Lagrangian point of the orbit to do so.…”
Section: Introductionmentioning
confidence: 99%
“…25 in Verbunt, 1993), is large enough to generate the dynamo effect resulting in a net magnetic field anchored into the companion star surface (see Nelson & Rappaport, 2003). The mass accretion rate predicted by the theory of secular evolution, under the assumed hypothesis, is given by the relation of Burderi et al (2010) (see also Di Salvo et al, 2008):…”
Section: Discussionmentioning
confidence: 99%